Cash holdings in the global hotel industry: Do managers act with bounded rationality when they cannot find optimal solutions? - Theodoros V. Stamatopoulos (Contemporary Economics, 2022)
The purpose of this paper is to contribute the relevant literature solving the puzzle of the excessive corporate cash. There are serious reasons to develop the falsifiable hypothesis "managers in the global hotel industry, act with bounded rationality in holding cash, when they cannot find optimal solutions". First, it is explained why it is logical to have deviations from the neoclassical expected utility theory, coming not to be fully rational behavior. Second, it is shown that in complex and uncertain hotel industry's environment, the decision making is better explained through the bounded rationality hypothesis (BRH), involving a search for alternatives, satisficing (satisfy + suffice), and adapting aspirations. Along with behavior-based economic theory, it seems that BRH can complete the trade-off and pecking order optimization-based models, that prevail the relevant literature, within the current economic "paradigm". From a global sample of panel data of hotel industry for the period 2001-2018, the paper detects bounded rational behavior statistically, by not rejecting the null of relevant variables' equal means in the tails of the cash distribution, and econometrically, by similarly estimated parameters to unrestricted and restricted models. Having found strong evidence in favour of the BRH for the "profitability" factor, balanced evidence for both boundedly and fully rational managers' behavior, for the "value" and "investments" factors, while, no-evidence for the BRH in the case of the "size" factor. Thus, the complementarity of optimal with Simon's satisficing solutions in the relevant cash management can benefit both investors and policy makers.
Keywords: B4; C58; G03; G32; G34; 330; cash holdings; hotel firms globally; bounded rationality hypothesis; Kuhn's paradigm; panel data econometrics